(untitled) (Research, Society and Development, 2021)
The epidemiology of gastrointestinal nematodes was studied in 120 breeds sheep of races Lacaune, Creole and their crosses in a semi-intensive grazing regime in private property, in Santana do Livramento, West Frontier of Rio Grande so Sul. The climate in the region is Cfa and the experimente was conducted for twelve months, crossing for four seasons of the year. The animals had natural infection by distincts species of helminths and the work was based on the egg count per gramo f feces (OPG) of 30 animals, on average, and these, made up a pool of faces of the tem most infected for coproculture, in order to indicate the most prevalent generas in these samples. The data were analyzed using the Analysis of Variance test and the means were compared using the Skott-Knott test, a significance level of 5%. The most prvalent genera was Haemonchus sp. OPG data indicates that the peak of eggs production was in the spring. In addition, there was a tendency for parasites to resist anthelmintics in this property. In conclusion, there are more prevalente nematódeos generas in sheep farming avaible and was observed difference in the epidemiological distribution according to the season.